Monitoring and enforcement of climate policy - Hilary Sigman (Rutgers University, Department of Economics, 2010)
This chapter applies recent research on environmental enforcement to a potential U.S. program to control greenhouse gases, especially through emission trading. Climate policies present the novel problem of integrating emissions reductions that are relatively easy to monitor (such as carbon dioxide emissions from fossil fuels) with those that may be very difficult to monitor (such as some emissions of other greenhouse gases). The paper documents the heterogeneity in monitoring costs across different parts of current carbon markets. It argues that a broad emission trading system that includes more difficult-to-enforce components can provide less incentive to violate the law than a narrower program; thus, the government may not find it more costly to assure compliance with a broader program.
Keywords: 330; Klimaveränderung; Umweltpolitik; Treibhausgas; Emissionshandel; Messung; USA; EU-Staaten